Psychosocial Impact of Lock Down among College Students in Nagpur - Vaishali D. Tendolkar1 , Shaini Suraj2 , Harshala Rajurkar3 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Background: The deadly COVID 19 has brought the life to a standstill in many parts of the world. Theuncertainties in lives of people are increasing along with the spread and increasing death tolls due to disease.College students, the predominant youth are maximally affected by this crucial stage. Aim:The current studyaims at assessing the psychosocial impact of lock down among the college students.Study Design: Online survey.Study Population: College students in the age group of 17 to 25 years both male and females.Sample Size: 337.Material: Psychosocial Impact Scale for students developed by investigators (r=0.85).Results: The mean age of the students is 19.93+1.14. 96.4% students were living with their parentsduring the period of lock down. 36% experienced borderline negative impact and 20.17% reported mild tomoderate negative impact of lockdown in just 15 days of lock down period. Most surprisingly despite beingwith parents; 20.18% had been out on roads during lock down, 1.48 for their job, 36.80% for purchasingmedicines, 39.17% for grocery and vegetables, 4.75% to meet their friends, 2.37% to attend a funeral, 2.97%attended family function, 9.50% to complete their academic assignments, 13.65% to refresh themselves,12.76%to help neighbour/relatives.Conclusion: Lockdown has adversely affected the psychosocial status of the college students. Whileequipping for any disaster, a nation will have to find out strategies for rebuilding mental strength of itspeople after the disaster is over so as to enhance the return to normal functioning.